Development of exotic cultural tourism after the COVID-19 pandemic in Gunungsari Village Madiun Indonesia - Meilasari, Priska; Yustisiana, Rr. Arielia; Waluyo, Lorensius Anang Setiyo (Universitas Ahmad Dahlan, Yogyakarta, 2021)
This Society Service Program aimed to explore the unique tourism offered by Gunungsari Tourism Village of Kabupaten Madiun. Gunungsari people, through their Tourism Awareness Group (Kelompok Sadar Wisata) Sentono Taruno Puroboyo has offered Javanese Culture tourism packages which are branded as â€œBackdoor Tourismâ€ and â€œKampung Ajar Kejawenâ€. The programs arranged to develop this tourism village have been modified to fit in Covid 19 pandemic situation. The programs are documentary literature writing, Javanese culture-themed short story competition, bilingual travel guide, English for tourism training, protective health gear procurement for tourism place, Javanese manuscript writing on lontar leaves, and decorative display made of â€œJanur Kuningâ€ (young leaf of big palm tree) through youtube channel, and digital technology training. Therefore, some methods and approaches are used in this program, including Participatory Rural Appraisal, Participatory Technology Development, Community Development, persuasive, and educative. This program has equipped Pokdarwis members with enough knowledge to communicate in English, manage the website and youtube channel, and supply their protective health gear. The direct impact of this program on Gunungsari tourism is the significant increase in the number of visitors coming on-site by applying strict health protocol in the tourism place to ensure tourist security.